China's practical wisdom: Assumption of liability for endangering public health in bankruptcy proceedings—A case study of the Changchun Changsheng Biotechnology vaccine incident and the Johnson & Johnson baby powder incident - Huang, Chaoyi (Frontiers in Public Health, 2022)
The assumption of liability for endangering public health has always been a legislative challenge in bankruptcy proceedings. Although it has been theoretically proven that the tort creditor should hold a position higher than that of unsecured creditors in bankruptcy proceedings, both legislation and judicial practice have been found wanting in many countries. China has witnessed large-scale domestic public health incidents where the tort debtor has entered bankruptcy proceedings while the tort claims were being settled. In Changchun Changsheng Biotechnology vaccine incident, to maintain social order and protect the rights and interests of the tort creditor, the Chinese government required the tort debtor to set up a special compensation fund of RMB 500 million and hand it over to a third party for management. This approach was mainly adopted because tort creditors can only participate in the bankruptcy distribution as an unsecured creditor, according to the Enterprise Bankruptcy Law of China, and as a result, their rights and interests cannot be guaranteed. In the context of the Enterprise Bankruptcy Law of China, this approach face predicaments of legitimacy and effectiveness. Moreover, even if the legislators follow scholars' advice and grant the tort creditor priority in bankruptcy proceedings, that would still not be enough to protect the rights and interests of the tort creditor, not to mention the possibility that the tort debtor might follow the example of Johnson & Johnson to avoid liability in practice. In fact, the Chinese government's approach is similar to that of Johnson & Johnson's, but more advisable. The Enterprise Bankruptcy Law of China (Bill of Amendment) will be submitted to the Standing Committee of the National People's Congress for preliminary deliberation this year, and the Chinese government's approach to the Changchun Changsheng vaccine case is very likely to be codified. This will resolve the predicaments of legitimacy and effectiveness that the government's current approach is facing and serve as a point of reference for the future revision of U.S. bankruptcy law and the handling of related cases.